1976
DOI: 10.1111/j.1365-2621.1976.tb00767_41_4.x
|View full text |Cite
|
Sign up to set email alerts
|

Nitrite Binding Sites on Myoglobin

Abstract: 1 SN-labelled nitrite was used to determine the amount of nitric oxide bound to unheated compared to heated myoglobin. Heated samples contained twice the amount of 1 5N as unheated samples. The globin portion was likely detached from the myoglobin by heating, and two sites for binding of nitric oxide were therefore made available.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

1979
1979
2016
2016

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(9 citation statements)
references
References 6 publications
0
9
0
Order By: Relevance
“…During heating, the globm portion of the myoglobin is denatured and detached. This then allows the addition of a second nitric oxide molecule on the iron atom of the iron-porphyrin ring as confirmed by the use of N15 labelled nitrite (Lee and Cassens, 1976;Renerre and Rouge, 1979).…”
Section: Introduction Nitritementioning
confidence: 92%
“…During heating, the globm portion of the myoglobin is denatured and detached. This then allows the addition of a second nitric oxide molecule on the iron atom of the iron-porphyrin ring as confirmed by the use of N15 labelled nitrite (Lee and Cassens, 1976;Renerre and Rouge, 1979).…”
Section: Introduction Nitritementioning
confidence: 92%
“…It showed that the level of formulated fresh celery leaves and applied incubation temperature did not appear to be as important as the amount of time required for enzyme of nitrate reductase of fresh celery leaves or fresh beef to convert nitrate to nitrite and then into nitric oxide (NO) to result in cured pigment development. Lee & Cassens (1976) concluded that a minimum of two hours of incubation is required to convert 90% of nitrite to nitric oxide (NO) and bound with myoglobin to nitrosylmyoglobin formation. According to Cassens et al (1979) and Shahidi & Pegg (1992), after heating, the globin portion of nitrosylmyoglobin were denatured and escaped from the iron atom to form stable nitrosylmyochrome or nitrosylhemochrome.…”
Section: Cured Pigment and Total Pigmentmentioning
confidence: 99%
“…It is difficult to control composition and properties of raw meat, but the interaction of meat quality and processing parameters should be recognized since the natural properties of meat may be utilized for some control of residual nitrite. Lee et al (1976) showed that samples made with white muscle had lower residual nitrite than those from red musdie. They found that this difference resulted from the high pH of the red muscle.…”
Section: Reactivity Of Nitrite In Meat Curingmentioning
confidence: 97%
“…Cavlek et al (1974) reported that nitrite decomposition was found to be closely related to nitrosomyoglobin forma tion in beef upon heating. Lee and Cassens (1976) showed that heated myoglobin had twice as much as unheated samples when labelled NaNOg was incubated with myoglobin. It has been shown that the amount of nitric oxide bound to myoglobin increased with increasing temperature and time (Renerre and Rougie, 1979).…”
Section: Temperature Effect On Nitritementioning
confidence: 99%